Dental caries and the nutritional status of preschool children: a spatial analysis - Campos, Juliana Alvares Duarte Bonini [UNESP]; Melanda, Edson Augusto; Antunes, Juliana da Silva; Foschini, Ana Lígia Rozato [UNESP] (Associação Brasileira de Saúde Coletiva (ABRASCO), 2011)
OBJETIVO: analisar espacialmente a distribuição da cárie dentária e do estado nutricional (EN) de pré-escolares, de 5 anos de idade do município de Araraquara, SP. MÉTODOS: Trata-se de estudo transversal com delineamento amostral probabilístico estratificado. Realizou-se exame clínico bucal para investigação do Índice ceod. Indicadores de peso para altura (P/A), altura para idade (A/I), peso para idade (P/I) e Índice de Massa Corpórea (IMC) foram calculados para classificação do EN. Realizou-se análise estatística descritiva e confeccionou-se mapa temático. Ao final do estudo 491 crianças possuíam codificação completa de endereço. A captura dos pontos de referencial geográfico foi realizada com o auxílio de aparelho de GPS. Elaborou-se semivariograma omini-direcional. RESULTADOS: Observa-se que ambas variáveis apresentaram efeito pepita puro, ou seja, os valores da semi-variância oscila em torno da variância dos dados. Isso implica que as variáveis não são regionalizadas, sendo assim, seus valores não possuem dependência espacial direta. CONCLUSÃO: Cárie dentaria e estado nutricional são condições que não apresentam dependência espacial. Eventualmente a combinação destes indicadores com outros pode produzir efeitos de dependência espacial.

OBJECTIVE: This cross-sectional study sought to conduct a spatially analysis of the distribution of dental caries and the nutritional status (NS) of 5-year-old preschool children of public schools in the city of Araraquara, São Paulo, Brazil. METHODS: The sample was selected in a stratified probabilistic manner. A dental examination was conducted to investigate the dmft index. The anthropometric indicators of the weight/height (W/H), height/age (H/A), weight/age (W/A) and body mass index (BMI) were calculated to estimate the NS. A descriptive statistical analysis was conducted and a thematic map was created. At the end of the study 491 children had full address codification. A GPS device was used to ascertain the geographic reference points. A pluri-directional semi-variogram was elaborated. RESULTS: It was revealed that both variables presented a pure nugget effect showing the absence of a spatial correlation, in other words the dmft and nutritional status are not regionalized variables, and their values do not reveal direct spatial dependence. CONCLUSIONS: Dental caries and nutritional status are health conditions that do not reveal spatial dependence. Ultimately, the combination of these indicators with others can produce spatial dependence effects.
Cárie dental e estado nutricional de pré-escolares: análise espacial
Keywords: Antropometria; Cárie dentaria; Geoestatística; Estado Nutricional; Análise Espacial; Anthropometrics; Dental caries; Geostatistics; Nutritional Status; Spatial Analysis